2011
DOI: 10.5012/bkcs.2011.32.10.3571
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Control of Single Crystalline Rutile TiO2Nanowires

Abstract: Nano-scaled metal oxides have been attractive materials for sensors, photocatalysis, and dye-sensitization for solar cells. We report the controlled synthesis and characterization of single crystalline TiO2 nanowires via a catalyst-assisted vapor-liquid-solid (VLS) and vapor-solid (VS) growth mechanism during TiO powder evaporation. Scanning electron microscope (SEM) and transmission electron microscope (TEM) studies show that as grown TiO2 materials are one-dimensional (1D) nano-structures with a single cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Using Ni catalyst on Ti substrate and TiO 2 powder as source, Park et al [18] claimed that their mechanism is VLS. Baik et al also did the same experiment and argued that ''although the presence of a small catalyst particle implies a VLS growth mechanism, number of observations suggest that the mechanism differs somewhat from the VLS process as it is normally understood.…”
Section: The Materials B (C) Diffuses Toward the Outside (Inside)mentioning
confidence: 99%
See 3 more Smart Citations
“…Using Ni catalyst on Ti substrate and TiO 2 powder as source, Park et al [18] claimed that their mechanism is VLS. Baik et al also did the same experiment and argued that ''although the presence of a small catalyst particle implies a VLS growth mechanism, number of observations suggest that the mechanism differs somewhat from the VLS process as it is normally understood.…”
Section: The Materials B (C) Diffuses Toward the Outside (Inside)mentioning
confidence: 99%
“…In second method (2), observing gold droplets over nanowires, Mortezaali et al [15] and Park et al [18] have determined the growth mechanism of their method as VLS (2.1). They also considered the Ti substrate as Ti vapor source.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…There are previous studies of nanowire growth using Vapor-Liquid-Solid (VLS) process with metal catalyst [13][14][15][16][17][18][19][20]. Generally, it is reported that TiO2 nanowire grows at 800∼900 o C using VLS process.…”
Section: Introductionmentioning
confidence: 99%